A Rare Mechanism Of Globe Injury In Badminton Player - Atul Kumar Singh; Ashish Pandey; S Mohan (Delhi Journal of Ophthalmology)
Closed globe injuries due to shuttlecock are reported, but open globe injury due to shuttlecock in a badminton player wearing glasses have not been reported. We report an unusual case of open globe injury due to shuttlecock breaking the spectacles of a player. A 22 years old male presented with sudden onset diminution of vision in the right eye following trauma by a shuttlecock which shattered his spectacles, while playing singles in badminton. He was diagnosed as a case of open globe injury with full-thickness corneoscleral tear. Primary globe repair was done under general anaesthesia. Postoperative visual recovery was good. This is a unique case resulting from the shuttlecock shattering the patientʼs glasses leading to an open globe injury. To the best our knowledge, this is the first case report from India presenting with full-thickness scleral rupture indirectly from shuttlecock injury